2020
DOI: 10.3390/ijms21124503
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Neuroimaging Approaches to Understanding Post-Traumatic Stress Disorder

Abstract: Post-traumatic stress disorder (PTSD) is a highly disabling condition, increasingly recognized as both a disorder of mental health and social burden, but also as an anxiety disorder characterized by fear, stress, and negative alterations in mood. PTSD is associated with structural, metabolic, and molecular changes in several brain regions and the neural circuitry. Brain areas implicated in the traumatic stress response include the amygdala, hippocampus, and prefrontal cortex, which play an essential role in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 98 publications
(110 reference statements)
1
18
0
7
Order By: Relevance
“…Posttraumatic stress disorder (PTSD) is a complex condition that develops after exposure to a serious and often life-threatening event (Nisar et al, 2020). Core symptoms include avoidance, hyperarousal, reexperiencing, and negative alterations in mood and cognition.…”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%
“…Posttraumatic stress disorder (PTSD) is a complex condition that develops after exposure to a serious and often life-threatening event (Nisar et al, 2020). Core symptoms include avoidance, hyperarousal, reexperiencing, and negative alterations in mood and cognition.…”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%
“…Post-traumatic stress disorder (PTSD) is a complex condition that develops after exposure to a serious and often life-threatening event [Nisar et al, 2020]. The lifetime prevalence of PTSD is significantly higher for females (2.6%) than males (1.0%) cross-nationally (N=71,083) [Koenen et al, 2017], with around twice the prevalence for females (lifetime=6.1%, 12-month=6.1%) than males (lifetime=4.1%, 12-month=3.2%) in the US [Goldstein et al 2016], despite experiencing similar numbers of traumatic events [Lehavot et al, 2018].…”
Section: Post-traumatic Stress Disordermentioning
confidence: 99%
“…Although the understanding of the molecular mechanism of PTSD has made great progress over the years, the exact pathogenesis is still unclear. MRI examination of PTSD patients showed that the hippocampus volume decreased (Milani et al 2017;Moyer 2016;Nisar et al 2020), animal experiments also found that the hippocampus of PTSD was closely related to the memory loss after a long delay (Joshi et al 2020; Shan et al 2020). The above results show that the abnormality of hippocampus were the important pathogenesis of PTSD.…”
Section: Discussionmentioning
confidence: 99%